Sociodemographic determinants and mosquito nest eradication practices of dengue hemorrhagic fever in indonesia: Findings from the Indonesian Health Survey 2023 - Ikrimah Diyan Lestari; Evi Susanti Sinaga (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Dengue Hemorrhagic Fever (DHF) is widely distributed in tropical regions and remains a public health concern in Indonesia In 2023, Indonesia reported 114,720 DHF cases with 894 deaths. The occurrence of DHF is influenced by multiple factors, including environmental conditions and community behavior that can be modified through prevention efforts. Puspose: To analyze the association between sociodemographic factors and mosquito nest eradication behavior with the prevalence of DHF in Indonesia. Method: This study employed a cross-sectional design using secondary data from the Indonesian Health Survey 2023, involving 877,531 respondents. Statistical analysis was performed using the Pearson Chi-Square test. Results: There is a significant association between age, place of residence, covering water storage containers, destroying used items, applying larvicide powder to water storage containers, installing mosquito nets on house ventilation, and using mosquito repellents with the prevalence of DHF (p <0.05). Meanwhile, gender, education, and draining bathtubs/large buckets/drums were not significantly associated with the prevalence of DHF (p >0.05). Conclusion: Sociodemographic factors, including age and place of residence, as well as mosquito nest eradication behaviors covering water storage containers, destroying used items, applying larvicide powder to water storage containers, installing mosquito nets on house ventilation, and using mosquito repellents were significantly associated with DHF prevalence. Based on these results, strengthening targeted mosquito nest eradication interventions and public health programs that consider age and residential characteristics is recommended to support DHF prevention efforts in Indonesia.